Optimalisasi Kompetensi Mahasiswa Bisnis Digital Melalui Kunjungan Dan Kolaborasi Dengan RLA Creative & Digital Marketing Agency - Nur Azizah; Zulfitri Yani; Siti Azzahra (CV. Multi Kreasi Media, 2025)
This community service activity aims to enhance the practical competencies of students in the D4 Digital Business Study Program through a field visit to RLA Creative & Digital Marketing Agency. Designed to bridge classroom learning with the real-world demands of the digital industry particularly in digital marketing this initiative provides students with hands-on experiences through direct observation, interactive discussions, and presentations by industry professionals. The activity offers contextual and practical insights into digital marketing strategies, content management, and brand development. The outcomes indicate an improved understanding among students of the dynamics within the creative digital industry, while also paving the way for sustainable collaborations, such as internship programs, industry-based projects, and curriculum development aligned with market needs. This initiative serves as a strategic effort to foster synergy between higher education institutions and the industry in producing competent graduates who are well-prepared to meet the challenges of the digital era.